MEA learning model impact on Pancasila education outcomes based on motivation level - Khairunnisa Rizka; Daulat Saragi; Abdul Murad (Inovasi Kurikulum, 2025)
Learning outcomes in Pancasila and Citizenship Education (Pendidikan Pancasila dan Kewarganegaraan or PPKn) among elementary students still face challenges, particularly due to the use of less innovative learning models and low student motivation. This study aims to examine the differences in PPKn learning outcomes between students taught using the Means-Ends Analysis (MEA) model and those taught using the expository model, as well as the differences based on learning motivation levels and the interaction between learning models and motivation on learning outcomes. The study employed a quasi-experimental method with a two-by-two factorial design, involving fourth-grade students at SD Swasta Tunas Harapan Islam Medan. The results showed that students taught with the MEA model achieved better learning outcomes than those using the expository model. Students with high motivation also performed better than those with low motivation. Furthermore, a significant interaction was found between learning models and motivation levels, with the combination of the MEA model and high motivation yielding the most optimal outcomes. In conclusion, the MEA model is more effective in improving PPKn learning outcomes, especially for students with high motivation. These findings highlight the importance of selecting suitable learning models and taking into account students’ internal factors to support learning success.   Abstrak Hasil belajar Pendidikan Pancasila dan Kewarganegaraan (PPKn) pada peserta didik sekolah dasar masih menghadapi tantangan, terutama karena penggunaan model pembelajaran yang kurang inovatif dan rendahnya motivasi belajar. Penelitian ini bertujuan untuk menganalisis perbedaan hasil belajar PPKn antara peserta didik yang menggunakan model pembelajaran Means Ends Analysis (MEA) dan peserta didik dengan model ekspositori, perbedaan berdasarkan tingkat motivasi belajar, serta interaksi antara model pembelajaran dan motivasi belajar terhadap hasil belajar. Penelitian menggunakan metode eksperimen semu dengan desain faktorial dua kali dua, melibatkan peserta didik kelas IV SD Swasta Tunas Harapan Islam Medan. Hasil penelitian menunjukkan bahwa peserta didik yang mengikuti pembelajaran dengan model MEA memiliki hasil belajar lebih tinggi dibandingkan dengan peserta didik yang menggunakan model ekspositori. Peserta didik dengan motivasi belajar tinggi juga menunjukkan pencapaian lebih baik dibandingkan peserta didik yang bermotivasi rendah. Selain itu, terdapat interaksi signifikan antara model pembelajaran dan motivasi belajar, di mana kombinasi model MEA dan motivasi tinggi menghasilkan capaian belajar paling optimal. Simpulan dari penelitian ini menegaskan bahwa model MEA efektif dalam meningkatkan hasil belajar PPKn, terutama pada peserta didik dengan motivasi belajar tinggi. Temuan ini menyoroti pentingnya pemilihan model pembelajaran yang tepat dan perhatian terhadap faktor internal peserta didik dalam mendukung keberhasilan pembelajaran. Kata kunci: hasil belajar PPKn; model pembelajaran MEA; motivasi belajar; pendidikan Pancasila; sekolah dasar